Sie sind auf Seite 1von 11

PHY4604 Fall 2007 Problem Set 4 Solutions

PHY 4604 Problem Set #4 Solutions


Problem 1 (25 points):.
(a) (2 points) Show that the sum of two hermitian operators is hermitian.
Solution: If (Aop)↑ = Aop and (Bop)↑ = Bop then (Aop+Bop)↑ = (Aop)↑+(Bop)↑= (Aop+Bop).
(b) (2 points) Suppose that Hop is a hermitian operator, and α is a complex number. Under what
condition (on α) is αHop hermitian?
Answer: α is real
Solution: (αHop) ↑ = α∗(Hop) ↑=α∗Hop. Thus, αHop hermitian provided α = α∗ (i.e. α is real).
(c) (2 points) When is the product of two hermitian operators hermitian?
Answer: When the two operators commute.
Solution: If (Aop)↑ = Aop and (Bop)↑ = Bop then
(AopBop)↑ = (Bop)↑ (Aop)↑= Bop Aop= Aop Bop + [Bop, Aop]
and (AopBop)↑ = Aop Bop provided [Bop, Aop] = 0. Note that I used (e).
d ↑
(d) (2 points) If Oop = , what is Oop ?
dx
↑ d
Answer: Oop =−
dx
Solution: We know that
∞ ∞

∫ [O ] ∫ Ψ ( x , t )O
* ↑
op Ψ2 ( x, t ) Ψ1 ( x, t ) dx = Ψ1 ( x, t ) dx
*
2 op
−∞ −∞
We see that
∞ ∞
dΨ2∗ ( x, t ) dΨ ( x , t )
∫− ∞ dx Ψ1 ( x, t )dx = − −∫∞ Ψ2 ( x, t ) 1dx dx
*

where I integrated by parts and dropped the boundary term. Thus,


↑ d
Oop =− .
dx
↑ ↑ ↑
(e) (2 points) Show that ( Aop Bop ) = Bop Aop .
Solution: We know that <ψ1|(AopBop)|ψ2>* = <ψ2|(AopBop)↑|ψ1>, but
<ψ1|(AopBop)|ψ2>* = <ψ1|Aop|Bψ2>* = < Bψ2|(Aop)↑| ψ1> = < ψ2|(Bop)↑ (Aop)↑| ψ1>,
where I used |Bψ2> = Bop|ψ2> and <Bψ2| = <ψ2|(Bop)↑.
(f) (2 points) Prove that [AB,C] = A[B,C] + [A,C]B, where A, B, and C are operators.
Solution: We see that
[AB,C] = ABC – CAB
A[B,C] + [A,C]B = A(BC-CB) + (AC-CA)B = ABC - CAB
df
(g) (2 points) Show that [( p x ) op , f ( x)] = −ih , for any function f(x).
dx
Solution: We see that
d dψ
[( px )op , f ( x)]ψ ( x) = −ih ( fψ ) + ihf
dx dx
df dψ dψ df
= −ih ψ − ihf + ihf = −ih ψ ( x)
dx dx dx dx

Department of Physics Page 1 of 11


PHY4604 Fall 2007 Problem Set 4 Solutions

(h) (2 points) Show that the anti-hermitian operator, Iop, has at most one real eigenvalue (Note:

anti-hermitian means that I op = − I op ).
Solution: We see that if Iop|ψ> = λ|ψ> then λ = <ψ|Iop|ψ> and
λ∗ = (<ψ|Iop|ψ>)* = <ψ|(Iop) ↑|ψ> = -<ψ|Iop|ψ> = -λ.
If we let λ = x+iy then λ∗ = x-iy and λ∗ = -λ implies that x-iy = -x-iy or 2x= 0. The only real
eigenvalue is λ = 0.
(i) (2 points) If Aop is an hermitian operator, show that < Aop2 >≥ 0 .
Solution: The norm of any allowed state is positive definite. Namely,
0 ≤ <Aψ|Aψ> = <ψ|(Aop)↑ Aop |ψ> = <ψ|(Aop)2 |ψ> = <(Aop)2>,
where I used |Aψ> = Aop|ψ> and <Aψ| = <ψ|(Aop)↑ and (Aop)↑ = Aop.

(j) (2 points) The parity operator, Pop, is defined by PopΨ(x,t) = Ψ(-x,t). Prove that the parity
operator is hermitian and show that Pop2 = 1 , where 1 is the identity operator. Compute the
eigenvalues of the parity operator.
Solution: An operator is hermitian if
∞ ∞

∫ [O ] ∫ Ψ ( x , t )O
*
op Ψ2 ( x, t ) Ψ1 ( x, t ) dx = Ψ1 ( x, t ) dx
*
2 op
−∞ −∞
If we let Oop = Pop we get
∞ ∞ ∞ ∞

∫ [P Ψ ( x, t )] Ψ ( x, t )dx = ∫ Ψ (− x, t )Ψ ( x, t )dx = ∫ Ψ ( x, t )Ψ (− x, t )dx = ∫ Ψ ( x, t ) P Ψ ( x, t )dx


* * * *
op 2 1 2 1 2 1 2 op 1
−∞ −∞ −∞ −∞
where I changed variables x → -x in the integration. Note that
(Pop)2Ψ(x,t) = (Pop) (Pop)Ψ(x,t) = (Pop) Ψ(-x,t) = Ψ(x,t). Thus, Pop2 = 1 .
If Pop|ψ> = λ|ψ> where λ is real since Pop is hermitian. Also, (Pop)2|ψ> = λ2|ψ>, but
(Pop)2|ψ> = 1|ψ> which implies that λ2 = 1 and hence λ = ±1
(k) (2 points) Idempotent operators have the property that Pop2 = Pop . Determine the eigenvalues
of the idempotent operator Pop and characterize its eigenvectors.
Solution: Here we have Pop|ψ> = λ|ψ> and (Pop)2|ψ> = λ2|ψ> = Pop|ψ> = λ|ψ> thus λ2 = λ or
λ(λ -1) = 0 and hence λ = 0 or λ = 1. Let |ψ1> be the eigenket of Pop with eigenvalue 1 and |ψ0>
be the eigenket of Pop with eigenvalue 0. Thus, Pop |ψ1> = |ψ1> and Pop|ψ0> = 0. Any (complex)
multiple of |ψ1> (i.e. α|ψ1>) is an eigenket of Pop with eigenvalue 1. Any ket orthogonal to |ψ1>
is an eigenket of Pop with eigenvalue 0.
↑ ↑
(l) (3 points) Unitary operators have the property that U op U op = U opU op = 1 , where 1 is the
identity operator. Show that the eigenvalues of a unitary operator have modulus 1. Show that if
<Ψ|Ψ> = 1 then <UΨ|UΨ> = 1 (i.e. unitary transformations preserve inner products). Prove that
iA
if Aop is hermitian then e op is unitary.
Solution: We see that 1 = <Ψ|Ψ> = <Ψ|1|Ψ> = <Ψ|(Uop)↑Uop|Ψ> = <UΨ|UΨ>,
where I used |Uψ> = Uop|ψ> and <Uψ| = <ψ|(Uop)↑. Now let
∞ (iA ) n ∞ ( −iA↑ ) n
U op = e op = ∑ op and U op == ∑
↑ − iA ↑ − iA
= e op = e op ,
iA op

n =1 n! n =1 n!

where I used (Aop) = Aop. Now we see that

Department of Physics Page 2 of 11


PHY4604 Fall 2007 Problem Set 4 Solutions

↑ − iAop
U op = e = 1 and Uop is unitary.
iAop
U op e

Problem 2 (15 points): Schrödinger’s equation says


∂Ψ ( x, t )
H op Ψ ( x, t ) = ih ,
∂t
where the Hamiltonian operator is given by H op = p x2 / 2m + V ( x) .
(a) (2 points) Prove that Hop is hermitian.
Solution: An operator is hermitian if
∞ ∞

∫ [O ] ∫ Ψ ( x , t )O
*
op Ψ2 ( x, t ) Ψ1 ( x, t ) dx = *
2 op Ψ1 ( x, t ) dx
−∞ −∞

1 ∂2
If we let Oop = H op = + V ( x) then
2m ∂x 2
*

⎡⎛ 1 ∂ 2

⎞ ⎤
∫− ∞ [
H op Ψ2 ( x , t ) Ψ1 (]
*
x , t ) dx = ∫− ∞ ⎣⎜⎝ 2m ∂x
⎢ ⎜ 2
+ V ( x ) ⎟
⎟ Ψ2 ( x , t ) ⎥ Ψ1 ( x, t ) dx
⎠ ⎦
∞ ∞
1 ∂ 2 Ψ2∗ ( x, t )
= ∫
2m − ∞ ∂x 2
Ψ1 ( x, t ) dx + ∫ V ( x ) Ψ2∗ ( x, t ) Ψ1 ( x, t ) dx =
−∞
∞ ∞
1 ∂Ψ2∗ ( x, t ) ∂Ψ1 ( x, t )
=− ∫
2m − ∞ ∂x ∂x
dx + ∫ Ψ2∗ ( x, t )V ( x ) Ψ1 ( x, t ) dx
−∞
∞ ∞
1 ∂ 2 Ψ1 ( x, t )
∫ dx + ∫ Ψ2∗ ( x, t )V ( x ) Ψ1 ( x, t ) dx

= Ψ2 ( x , t )
2m − ∞ ∂x 2
−∞
∞ ∞
⎛ 1 ∂2 ⎞
= ∫ Ψ ( x, t )⎜⎜

2 + V ( x ) ⎟⎟Ψ1 ( x, t ) dx = ∫ Ψ2∗ ( x, t ) H op Ψ1 ( x, t ) dx
−∞ ⎝ 2 m ∂x 2
⎠ −∞
where I integrated by parts twice and dropped the boundary terms.
(b) (5 points) Prove that
d i ∂O
< Oop >= < [ H op , Oop ] > + < op > .
dt h ∂t
If the operator Oop does not depend explicitly on time and if it commutes with the Hamiltonian,
then <Oop> is constant in time (i.e. it is conserved).
Solution: We see that

Department of Physics Page 3 of 11


PHY4604 Fall 2007 Problem Set 4 Solutions


d <O> d
= ih ∫ Ψ ( x , t )O Ψ ( x, t ) dx
*
ih op
dt dt −∞

⎛ ∂Ψ *
∂O ∂Ψ ⎞
= ih ∫ ⎜⎜ Oop Ψ + Ψ * op Ψ + Ψ *Oop ⎟ dx
− ∞⎝
∂t ∂t ∂t ⎟⎠
⎛⎛

∂Ψ ⎞

∂O ⎛ ∂Ψ ⎞ ⎞⎟

= ∫ ⎜ − ih ⎟ Oop Ψ + ihΨ * op Ψ + Ψ *Oop ⎜ ih ⎟ dx
⎜ ∂t ⎠ ∂t ⎝ ∂t ⎠ ⎟⎠
− ∞⎝ ⎝

∂O
= ih <
∂t
(
> + ∫ − ( H op Ψ )* Oop Ψ + Ψ *Oop H op Ψ dx )
−∞

∂O
= ih <
∂t
(
> + ∫ − Ψ * H op Oop Ψ + Ψ *Oop H op Ψ dx )
−∞

∂O
ih < > + ∫ Ψ * (Oop H op − H op Oop ) Ψ dx
∂t −∞

∂O
= ih < > + < [Oop , H op ] >
∂t
where I used
∂Ψ ( x, t ) ∂Ψ ∗ ( x, t )
ih = H op Ψ ( x, t ) and ih = − H op Ψ ∗ ( x, t ) ,
∂t ∂t
and since Hop is hermitian we know that
∞ ∞

∫ [H ] ∫ Ψ ( x, t ) H
*
op Ψ2 ( x, t ) Ψ1 ( x, t ) dx = Ψ1 ( x, t ) dx .
*
2 op
−∞ −∞

Thus,
d i ∂O
< Oop >= < [ H op , Oop ] > + < op > ,
dt h ∂t
and if Oop does not depend explicitly on time and if [Hop,Oop] = 0 then
d
< Oop >= 0 which implies that <Oop> is constant (i.e. independent of time).
dt
(c) (5 points) Prove that
d dV
< xop ( p x ) op >= 2 < T > − x ,
dt dx
where T is the kinetic energy operator (i.e. H = T + V).
Solution: If we let Oop = xop(px)op then from (b)

Department of Physics Page 4 of 11


PHY4604 Fall 2007 Problem Set 4 Solutions

d i i
< xop ( p x ) op >= < [ H op , xop ( p x ) op ] >= < [Top + V , xop ( p x ) op ] >
dt h h
i i
= < [Top , xop ( p x ) op ] > + < [V , xop ( p x ) op ] >
h h
= (< xop [Top , ( p x ) op ] > + < [Top , xop ]( p x ) op > + < xop [V , ( p x ) op ] > + < [V , xop ]( p x ) op > )
i
h
But
[Top , ( px ) op ] = 1
2m
2
[( p x )op , ( p x )op ] = 0
− ih
[Top , xop ] = 1
2m
2
[( p x ) op , xop ] = 1
2m ( p x ) op [( p x ) op , xop ] + 21m [( p x ) op , xop ]( p x ) op = ( px ) op
2m
dV
[V ( x), ( p x ) op ] = −[( px ) op ,V ( x)] = ih
dx
[V ( x), xop ] = 0
Thus,
< xop ( px )op >= (< xop [Top , ( px )op ] > + < [Top , xop ]( px )op > + < xop [V , ( px )op ] > + < [V , xop ]( px )op > )
d i
dt h
i ⎛ − ih dV ⎞ dV
= ⎜< ( px )op ( px )op > + < xopih > ⎟ =< 2T > − < x >
h⎝ m dx ⎠ dx
where I used Top = ( p x )op 2
/ 2m .
(d) (3 points) Use (c) to show that in a stationary state
dV
2 < T >= x .
dx
This is called the virial theorem.
Solution: For stationary states Ψ ( x, t ) = ψ ( x)e −iEt / h and hence
∞ ∞
< xop ( p x ) op >= ∫ Ψ ( x, t ) x ( p x ) op Ψ ( x, t ) dx = ∫ψ * ( x ) xop ( p x ) opψ ( x ) dx
*
op
−∞ −∞
which is independent of time so that for stationary states
d dV dV
< xop ( px )op >= 0 = 2 < T > − x and 2 < T >= x .
dt dx dx

Problem 3 (30 points): Consider an infinite square well defined by V(x) = 0 for 0 < x < L, and
V(x) = ∞ otherwise. The stationary state position-space wave functions are given by
2
Ψn ( x, t ) = ψ n ( x)e −iE n t / h with ψ n ( x) = sin( nπx / L)
L
n 2π 2h 2
and the eigenvalues are En = , and n is a positive integer.
2mL2
(a) (10 points) Find the momentum-space wave function Φ n ( px , t ) for the nth stationary state.
πL ne −iE n t / h
Answer: Φ n ( px , t ) =
h (nπ ) − ( px L / h)
2 2
(
1 − (−1) n e − ip x L / h )

Department of Physics Page 5 of 11


PHY4604 Fall 2007 Problem Set 4 Solutions

Solution: The momentum-space wave functions are given by


+∞ L
1 1 2 − iE n t / D
∫ ∫ sin(nπx / L)e − ip x x / D dx
− ip x x / D
Φ n ( px , t ) = Ψ ( x , t ) e dx = e
2πh − ∞ 2πh L
n
0

( − e − inπx / L )e − ip x x / D dx
L
1 2 − iE n t / D + inπx / L
=
2i 2πh L
e ∫
0
e

( )
L
1 2 − iE n t / D + i ( nπ / L − p x / h ) x
=
2i 2πh L
e ∫
0
e − e − i ( nπ / L + p x / h ) x dx

L
1 2 − iE n t / D ⎛ e + i ( nπ / L − p x / h ) x e − i ( nπ / L + p x / h ) x ⎞
= e ⎜⎜ + ⎟⎟
2i 2πh L ⎝ i (nπ / L − px / h) i (nπ / L + px / h) ⎠ 0
1 2 − iE n t / D ⎛ e + i ( nπ / L − p x / h ) L − 1 e − i ( nπ / L + p x / h ) L − 1 ⎞
= e ⎜⎜ + ⎟⎟
2i 2πh L ⎝ i (nπ / L − px / h) i (nπ / L + px / h) ⎠
1 2 − iE n t / D ⎛ (−1) n e − ip x L / h − 1 (−1) n e − ip x L / h − 1 ⎞
= e ⎜
⎜ (nπ − p L / h) L + (nπ + p L / h) L ⎟⎟
2 2πh L ⎝ x x ⎠
⎛ (nπ + px L / h) + (nπ − px L / h) ⎞
=−
1 L − iE n t / D
2 πh
e (
(−1) n e − ip x L / h − 1 ⎜⎜ ) ⎟⎟
⎝ (nπ − px L / h)(nπ + px L / h) ⎠
2nπ
=−
1 L − iE n t / D
2 πh
e (
(−1) n e − ip x L / h − 1 )
(nπ ) − ( px L / h) 2
2

πL ne − iE n t / D
=
h (nπ ) − ( px L / h)
2 2
1 − (−1) n e − ip x L / h ( )
Note that
⎧ cos( p x L / 2h ) n = 1,3,5L
(1 − (−1) e n − ip x L / h
)= e − ip x L /( 2 h )
(e + ip x L /( 2 h )
− (−1) n e − ip x L /( 2h ) = 2e − ip x L /( 2 h ) ⎨ )
⎩i sin( px L / 2h ) n = 2,4,6L
(b) (5 points) Graph ρ1 ( p x , t ) =| Φ1 ( p x , t ) |2 as a function of px for the ground state (i.e. n = 1).
4πL cos 2 ( p x L / 2h)
Answer: ρ1 ( p x , t ) = ρ1(px)
h [π 2 − ( px L / h) 2 ]2
Solution: For n = 1 we get
πL 2e −ip x L /( 2 h )e − iE n t / h
Φ1 ( px , t ) = cos( px L / 2h)
h π 2 − ( px L / h) 2
and
4πL cos 2 ( px L / 2h)
ρ1 ( px , t ) =| Φ1 ( px , t ) |2 = .
h [π 2 − ( px L / h) 2 ]2 -6.0 0.0 6.0

(c) (5 points) Graph ρ 2 ( px , t ) =| Φ 2 ( px , t ) |2 as a function of px for the 1st excited state (i.e. n = 2).

Department of Physics Page 6 of 11


PHY4604 Fall 2007 Problem Set 4 Solutions

16πL sin 2 ( px L / 2h)


Answer: ρ 2 ( px , t ) =
h [(2π ) 2 − ( px L / h) 2 ]2 ρ (p ) 2 x

Solution: For n = 2 we get


πL 4ie − ip x L /( 2 h )e −iE n t / h
Φ 2 ( px , t ) = sin( px L / 2h)
h (2π ) 2 − ( px L / h) 2
and
16πL sin 2 ( px L / 2h )
ρ 2 ( p x , t ) =| Φ 2 ( p x , t ) |2 = .
h [(2π ) 2 − ( px L / h ) 2 ]2
(d) (10 points) Use the momentum-space wave function
-1.0 0.0 1.0

Φ n ( px , t ) to calculate the expectation values of px and px2 for the nth stationary state and
compare your answer with your answer to problem set #2 problem 2(c).
n 2π 2h 2
Answer: < px > n = 0 and < px2 > n = same as before
L2
Solution: For even n we get

+∞ +∞
4n 2πL px cos 2 ( px L / 2h)
< px > n = ∫ px | Φ n ( px , t ) | dpx =
h −∫∞ [(nπ ) 2 − ( px L / h ) 2 ]2
2
dpx = 0
−∞
and for odd n we get
+∞ +∞
4n 2πL px sin 2 ( px L / 2h)
< px > n = ∫ px | Φ n ( px , t ) |2 dpx = ∫ dpx = 0
−∞
h −∞
[( nπ ) 2
− ( p x L / h ) 2 2
]
In both cases the integral vanishes because the integrand is odd under px → -px.
For even n we get

+∞ +∞
4n 2πL px2 cos 2 ( px L / 2h)
< px2 > n = ∫ px | Φ n ( px , t ) | dpx = h −∫∞ [(nπ ) 2 − ( px L / h) 2 ]2
2 2
dpx
−∞
2 +∞
4nh y 2 cos 2 (nπy / 2)
= 2
L ∫
−∞
(1 − y 2 ) 2
dy

and for odd n we get


+∞ +∞
4n 2πL px2 sin 2 ( px L / 2h)
< px2 > n = ∫ px | Φ n ( px , t ) | dpx = h −∫∞ [(nπ ) 2 − ( px L / h) 2 ]2
2 2
dpx
−∞
2 +∞
4nh y 2 sin 2 (nπy / 2)
=
L2 ∫
−∞
(1 − y 2 ) 2
dy

where y = px L /(nπh ) . These integrals can be evaluated by partial fractions as follows


y2 1⎛ 1 1 1 1 ⎞
= ⎜⎜ + + − ⎟.
( y − 1)
2 2
4 ⎝ ( y − 1) 2
( y + 1) 2
( y − 1) ( y + 1) ⎟⎠
For odd n

Department of Physics Page 7 of 11


PHY4604 Fall 2007 Problem Set 4 Solutions

+∞
y 2 cos 2 (nπy / 2)

−∞
(1 − y 2 ) 2
dy =

+∞ +∞ +∞ +∞
1 cos 2 (nπy / 2) 1 cos 2 (nπy / 2) 1 cos 2 (nπy / 2) 1 cos 2 (nπy / 2)
4 −∫∞ ( y − 1) 2
dy + ∫ dy + ∫ dy − ∫ dy
4 − ∞ ( y + 1) 2 4 − ∞ ( y − 1) 4 − ∞ ( y + 1)
But
+∞ +∞ +∞ k +∞
cos 2 (nπy / 2) cos 2 (nπ ( z m 1) / 2) sin 2 (nπz / 2) ⎛ nπ ⎞ sin 2 (u )
∫−∞ ( y ± 1)k dy = ∫−∞ z k
dz = ∫
−∞
z k
dz = ⎜
⎝ 2 ⎠
⎟ ∫ u k du
−∞
Where z = y ± 1 and u = nπz / 2 . Now
+∞
sin 2 (u ) ⎧0 k = 1
∫−∞ u k du = ⎨⎩π k = 2
Thus
+∞
cos 2 (nπy / 2) ⎧ 0 k =1
∫ (1 ± y)k
−∞
dy = ⎨
⎩nπ / 2 k = 2
2

and for n odd


4nh 2 nπ 2 n 2π 2h 2
< p x2 > n = = .
L2 4 L2
For even n we get
+∞ 2
y sin 2 (nπy / 2)
∫ (1 − y 2 )2 dy =
−∞
+∞ +∞ +∞ +∞
1 sin 2 (nπy / 2) 1 sin 2 (nπy / 2) 1 sin 2 (nπy / 2) 1 sin 2 (nπy / 2)
4 −∫∞ ( y − 1) 2
dy + ∫ dy + ∫ dy − ∫ dy
4 − ∞ ( y + 1) 2 4 − ∞ ( y − 1) 4 − ∞ ( y + 1)
But
+∞ +∞ +∞ k +∞
sin 2 (nπy / 2) sin 2 (nπ ( z m 1) / 2) sin 2 (nπz / 2) ⎛ nπ ⎞ sin 2 (u )
∫−∞ ( y ± 1)k dy = ∫−∞ z k
dz = ∫
−∞
z k
dz = ⎜
⎝ 2 ⎠
⎟ ∫ u k du
−∞
where z = y ± 1 and u = nπz / 2 .
Thus
+∞
sin 2 (nπy / 2) ⎧ 0 k =1
∫ (1 ± y)k
−∞
dy = ⎨
⎩nπ / 2 k = 2
2

and for n even


4nh 2 nπ 2 n 2π 2h 2
< p x2 > n = 2 =
L 4 L2

Problem 4 (20 points): Consider a three-dimensional vector space spanned by an orthonormal


basis |1>, |2>, |3>. “Ket” vectors |α> and |β> are given by
|α> = i|1> -2|2> -i|3> and |β> = i|1> + 2|3>.
(a) (5 points) Construct the “bra” vectors <α| and <β| in terms of the dual basis <1|, <2|, <3|.
Answer: <α| = -i<1| -2<2| +i<3| and <β| = -i<1| + 2<3|
(b) (5 points) Find <α|β> and <β|α> and confirm that <β|α> = <α|β>*.

Department of Physics Page 8 of 11


PHY4604 Fall 2007 Problem Set 4 Solutions

Answer: <α|β> = 1+2i and <β|α> = 1-2i and <β|α> = <α|β>*


Solution:
<α|β> = (-i<1| -2<2| +i<3|)( i|1> + 2|3>) = 1+2i
<β|α> = (-i<1| + 2<3|)( i|1> -2|2> -i|3>) = 1-2i
(c) (10 points) Construct all nine matrix elements of the operator Aop = |α><β|, in this basis, and
construct the matrix A. Is it hermitian?
⎛ 1 0 2i ⎞
⎜ ⎟
Answer: A = ⎜ 2i 0 − 4 ⎟ not hermitian
⎜ − 1 0 − 2i ⎟
⎝ ⎠
Solution:
A11 = <1|Aop|1> =<1 |α><β|1> = (i)(-i) = +1
A21 = <2|Aop|1> =<2 |α><β|1> = (-2)(-i) = +2i
A31 = <3|Aop|1> =<3 |α><β|1> = (-i)(-i) = -1

A12 = <1|Aop|2> =<1 |α><β|2> = (i)(0) = 0


A22 = <2|Aop|2> =<2 |α><β|2> = (-2)(0) = 0
A32 = <3|Aop|2> =<3 |α><β|2> = (-i)(0) = 0

A13 = <1|Aop|3> =<1 |α><β|3> = (i)(2) = +2i


A23 = <2|Aop|3> =<2 |α><β|3> = (-2)(2) = -4
A33 = <3|Aop|3> =<3 |α><β|3> = (-i)(2) = -2i

⎛ 1 0 2i ⎞ ⎛ 1 − 2i − 1⎞
⎜ ⎟ ↑ ∗
⎜ ⎟
A = ⎜ 2i 0 − 4 ⎟ A = ( AT ) = ⎜ 0 0 0 ⎟≠ A
⎜ − 1 0 − 2i ⎟ ⎜ − 2i − 4 2i ⎟
⎝ ⎠ ⎝ ⎠

Problem 5 (20 points): The Hamiltonian for a certain three-level system is represented by the
matrix
⎛a 0 b⎞
⎜ ⎟
H = ⎜0 c 0⎟
⎜b 0 a⎟
⎝ ⎠
where a, b, and c are real numbers.
(a) (5 points) What are the energy eigenvalues of this system (i.e. the allowed energies)?
Answer: E1 = c, E2 = a + b, and E3 = a – b.
Solution: We determine the eiganvalues by solving the determinate
a−λ 0 b
0 c−λ 0 =0
b 0 a−λ
Hence, (a - λ)(c – λ)(a – λ) – b2(c – λ) = 0 and the solution are l = c and (a – λ)2 = b2. Thus a – l
= ±b and the three energies are E1 = c, E2 = a + b, and E3 = a – b.
(b) (5 points) What are the (normalized) eigenvectors of H?

Department of Physics Page 9 of 11


PHY4604 Fall 2007 Problem Set 4 Solutions

⎛ 0⎞ ⎛1⎞ ⎛1⎞
⎜ ⎟ 1 ⎜ ⎟ 1 ⎜ ⎟
Answer: | E1 >= ⎜ 1 ⎟ | E2 >= ⎜ 0 ⎟ | E3 >= ⎜0⎟
⎜ 0⎟ 2⎜ ⎟ 2⎜ ⎟
⎝ ⎠ ⎝1⎠ ⎝ − 1⎠
Solution: For E1 = c we have
⎛ a 0 b ⎞⎛ x ⎞ ⎛ ax + bz ⎞ ⎛ x ⎞ ⎛ cx ⎞
⎜ ⎟⎜ ⎟ ⎜ ⎟ ⎜ ⎟ ⎜ ⎟
⎜ 0 c 0 ⎟⎜ y ⎟ = ⎜ cy ⎟ = c⎜ y ⎟ = ⎜ cy ⎟
⎜ b 0 a ⎟⎜ z ⎟ ⎜ bx + az ⎟ ⎜ z ⎟ ⎜ cz ⎟
⎝ ⎠⎝ ⎠ ⎝ ⎠ ⎝ ⎠ ⎝ ⎠
Thus, ax + bz = cx or (a-c)x +bz = 0 and bx + az = cz or bx + (a-c)z = 0 which implies that
[(a-c)2 – b2]x = 0 and thus x = 0 (provided that (a-c)2 ≠ b2) and
⎛ 0⎞
⎜ ⎟
| E1 >= ⎜ 1 ⎟ .
⎜ 0⎟
⎝ ⎠
For E2 = a + b we have
⎛ a 0 b ⎞⎛ x ⎞ ⎛ ax + bz ⎞ ⎛ x ⎞ ⎛ ( a + b) x ⎞
⎜ ⎟⎜ ⎟ ⎜ ⎟ ⎜ ⎟ ⎜ ⎟
⎜ 0 c 0 ⎟⎜ y ⎟ = ⎜ cy ⎟ = (a + b)⎜ y ⎟ = ⎜ (a + b) y ⎟
⎜ b 0 a ⎟⎜ z ⎟ ⎜ bx + az ⎟ ⎜ z ⎟ ⎜ ( a + b) z ⎟
⎝ ⎠⎝ ⎠ ⎝ ⎠ ⎝ ⎠ ⎝ ⎠
Thus, ax + bz = (a+b)x or -bx +bz = 0 and bx+az= (a+b)z or bx - bz = 0 and cy = (a+b)y which
implies that y = 0 and x = z.
⎛1⎞
1 ⎜ ⎟
| E2 >= ⎜ 0⎟ .
2⎜ ⎟
⎝1⎠
For E3 = a - b we have
⎛ a 0 b ⎞⎛ x ⎞ ⎛ ax + bz ⎞ ⎛ x ⎞ ⎛ ( a − b) x ⎞
⎜ ⎟⎜ ⎟ ⎜ ⎟ ⎜ ⎟ ⎜ ⎟
⎜ 0 c 0 ⎟⎜ y ⎟ = ⎜ cy ⎟ = (a − b)⎜ y ⎟ = ⎜ (a − b) y ⎟
⎜ b 0 a ⎟⎜ z ⎟ ⎜ bx + az ⎟ ⎜ z ⎟ ⎜ ( a − b) z ⎟
⎝ ⎠⎝ ⎠ ⎝ ⎠ ⎝ ⎠ ⎝ ⎠
Thus, ax + bz = (a-b)x or bx +bz = 0 and cy = (a-b)y which implies that y = 0 and x = -z.
⎛1⎞
1 ⎜ ⎟
| E3 >= ⎜ 0 ⎟.
2⎜ ⎟
⎝ − 1⎠
(c) (5 points) If the system starts out at t = 0 in the state

⎛0⎞
⎜ ⎟
| s (0) >= ⎜ 1 ⎟
⎜0⎟
⎝ ⎠
what is |s(t)> at later time t.

Department of Physics Page 10 of 11


PHY4604 Fall 2007 Problem Set 4 Solutions

⎛ 0⎞
− ict / h
⎜ ⎟
Answer: | s (t ) >=| E1 (t ) >= e ⎜1⎟
⎜ 0⎟
⎝ ⎠
Solution: In this case |s(0)> = |E1> and hence
⎛0⎞ ⎛0⎞
− iE 1 t / h
⎜ ⎟ − ict / h
⎜ ⎟
| s (t ) >= | E1 (t ) >= e ⎜1⎟ = e ⎜1⎟ .
⎜0⎟ ⎜0⎟
⎝ ⎠ ⎝ ⎠

(d) (5 points) If the system starts out at t = 0 in the state


⎛ 0⎞
⎜ ⎟
| s (0) >= ⎜ 0 ⎟
⎜1⎟
⎝ ⎠
what is |s(t)> at later time t.
⎛ − i sin(bt / h ) ⎞
− iat / h
⎜ ⎟
Answer: | s (t ) >= e ⎜ 0 ⎟
⎜ cos(bt / h ) ⎟
⎝ ⎠
Solution: In this case
1 1
| s (0) >= | E2 > − | E3 > .
2 2

and hence
⎛1⎞ ⎛1⎞
1 − iE 2 t / h 1 − iE3t / h 1 −i ( a + b )t / h ⎜ ⎟ 1 −i ( a −b )t / h ⎜ ⎟
| s (t ) >= e | E2 > − e | E3 >= e ⎜0⎟ − e ⎜0⎟
2 2 2 ⎜1⎟ 2 ⎜ − 1⎟
⎝ ⎠ ⎝ ⎠
⎛e − ibt / h
−e + ibt / h
⎞ ⎛ − i sin(bt / h) ⎞
1 − iat / h ⎜ ⎟ − iat / h ⎜ ⎟
= e ⎜ 0 ⎟=e ⎜ 0 ⎟
2 ⎜ e − ibt / h + e + ibt / h ⎟ ⎜ cos(bt / h) ⎟
⎝ ⎠ ⎝ ⎠

Department of Physics Page 11 of 11